Flesh wounds : the culture of cosmetic surgery - Blum, Virginia L., 1956- (EBSCO Academic Collection, 2003)
When did cosmetic surgery become a common practice, the stuff of everyday conversation? In a work that combines a provocative ethnography of plastic surgery and a penetrating analysis of beauty and feminism, Virginia L. Blum searches out the social conditions and imperatives that have made ours a culture of cosmetic surgery.